Critical analysis of the feasibility of strategic alliances in the context of Singapore's SMES - Ang, Bernard Kiang Yang (2008)
As globalization becomes more pervasive, Small and Medium-sized Enterprises (SMEs) in Singapore will face greater competition from both domestic as well as overseas players. This paper propose a framework to examine the feasibility of strategic alliances for the Singaporean SME based on four inter-linked dimensions of: needs, wants, achievability and sustainability.